Perancangan Sistem Arsip Digital menggunakan Fitur QR Code di BPJS Ketenagakerjaan Kabupaten Banyuwangi - Elsa Ayu Wardani; Ahmad Baijuri; Citra Ayu Pratiwi (SITEKNIK: Sistem Informasi, Teknik dan Teknologi Terapan, 2025)
Archive management at the BPJS Ketenagakerjaan (Employment Social security Agency) ini Banyuwangi Regency still faces challenges ini searching and tracking document. Manually stored archives often lead to delays ini service delivery and the risk of data loss. Therefore, a digital archive system ini needed to facilitate the process of recording, tracking, and reporting archive better. This study aims to create a digital archive system utilizing QR Codes using the SSADM method. The research steps include needs analysis, data model design, prosess flow design, and system interface design. The results show that the system can facilitate in managing archive searches using QR Codes, and improve efficiency and accuracy ini administrative processes.